Energy Analysis in Mechanised Rice Production System: Specifically for Central Thailand - Intaravichai, Pantipa (1998)
Rice has long been the most important food and served as a major source of employment in Thailand. Its yearly production is about 20 million metric tons from a total of 10 million hectares. This requires a large amount of energy inputs into the production process. A rice production system is here defined as any combination of field operations starting from ploughing, raking, levelling, planting, fertilising, spraying, pumping, and ending in harvesting. Each operation requires independent inputs in terms of fuel, indirect energy, and labour. These energy inputs are disbursed to the rice grower in the form of commercial energy and non-commercial energy. An improvement in energy allocation and management for a rice production system will assure the rice grower of a higher return. Understanding the current system of operation and improving one's power of prediction in terms of estimating the energy required are the best ways to improve a rice production system with regard to energy inputs allocation. A field study and a simulation study were carried out under this study. The central plain of Thailand was selected for the field survey and 150 rice growers were sampled and interviewed at random. The computer simulation programme was developed based on the classical theory of agricultural machinery management, as well as the empirical equations derived from this study. Fuel requirements, indirect energy requirements, and labour requirements were the main focus of interest. The simulated results yielded results consistent with those obtained from the field survey.